Pengaruh Pengungkapan Corporate Social Responsibility terhadap Kinerja Keuangan - Royhan Azwar; Nurleli (Bandung Conference Series: Accountancy, 2024)
Abstract. Disclosure of Corporate Social Responsibility is a company's commitment to the social, community, and environmental aspects surrounding its operations, which is crucial to consider in order to cultivate a positive image in the eyes of stakeholders. This research aims to determine the disclosure of Corporate Social Responsibility in food & beverage sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2022, to elucidate and analyze the extent of the influence of disclosure of Corporate Social Responsibility to financial performance proxied by Return on Assets (ROA) and Return on Equity (ROE) on food & beverage sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2022. The research method used is a verificative research method with a quantitative approach. Sample selection was conducted using purposive sampling, resulting in a sample of 30 companies. Data processing in this research is conducted using Eviews 12. The results of the research indicate that there is an influence between the variables of Corporate Social Responsibility disclosure and the level of company profitability proxied by Return on Assets (ROA) and Return on Equity (ROE) Abstrak. Corporate Social Responsibility adalah suatu komitmen perusahaan terhadap sosial, masyarakat, dan lingkungan sekitar perusahaan tersebut beroperasi yang penting untuk diperhatikan agar mendapatkan citra baik dimata stake holder. Penelitian ini bertujuan untuk mengetahui pengungkapan Corporate Social Responsibility pada perusahaan sektor food & beverage yang terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2022, untuk menjelaskan dan menganalisis seberapa besar pengaruh pengungkapan Corporate Social Responsibility terhadap kinerja keuangan yang di proksikan dengan Return on Assets (ROA) dan Return on Equity (ROE) pada perusahaan sektor food & beverage yang terdaftar di Bursa Efek Indonesia (BEI) periode 2018-2022. Metode penelitian yang digunakan adalah metode penelitian verifikatif dengan pendekatan kuantitatif. Pemilihan sampel menggunakan purposive sampling dan diperoleh sampel sebanyak 30 perusahaan. Pengolahan data dalam penelitian ini di olah menggunakan Eviews 12. Hasil penelitian menunjukkan bahwa adanya pengaruh antara variabel pengungkapan Corporate Social Responsibility terhadap tingkat profitabilitas perusahaan yang diproksikan dengan Return on Asset (ROA) dan Return on Equity (ROE).